146k views
5 votes
The sum of -2m and 3m is equal to the difference of 1/2 and 1/3

2 Answers

0 votes
Equation: -2m+3m=1/2-1/3

For you need to combine the like terms on each side. -2m+3m=1m. 1-2-1/3=1/6

Equation now: m=1/6
So your answer is 1/6
User Monstergold
by
5.9k points
4 votes

Hello!

Let's write out this problem symbolically:

-2m + 3m = (1/2) - (1/3)

m = (3/6) - (2/6) = 1/6

The sum of -2m and 3m is equal to the difference of 1/2 and 1/3 is m = 1/6.


User Karthikeyan Gopall
by
6.1k points